Desmopressin in vitro effects on platelet function, monitored with Multiplate, ROTEM and Sonoclot. (18th May 2016) - Pearson, Kevin; Jensen, Hanna; Kander, Thomas; Schött, Ulf
Abstract: Background and aims The vasopressin analogue desmopressin has demonstrated efficacy in decreasing bleeding time by increasing the circulating levels of coagulation factor VIII and von Willebrand factor, but also by direct effects on platelets. Previous studies have demonstrated contrasting results regarding the effect of desmopressin on platelets in vitro . The aim of this study was to investigate the dose-response effects of in vitro desmopressin in whole blood. Our hypothesis was that desmopressin could increase platelet function in anticoagulated whole blood being stored up to 4 hours.Methods Desmopressin was administered with up to four different concentrations to venous whole blood, sampled with standard vacutainer tubes from 10 healthy volunteers after consent. Platelet function was analyzed with three different point-of-care techniques: Multiplate platelet aggregometry with adenosine diphosphate, collagen, thrombin receptor activating peptide-6, ristocetin and arachidonic acid agonists, tissue factor-activated thromboelastometry and Sonoclot glass bead viscoelastic coagulation tests at baseline and 4 hours later using different activator reagents.Results Thromboelastometry and Sonoclot did not show any significant change between baseline and 4 h later. A significant decrease in area under curve (AUC) could be seen with the Multiplate between baseline and after 4 h. Desmopressin did not improve any of these tests at baseline or during a 4 h storage and incubation period.Conclusion In vitro administered desmopressin could not increase normal platelet function or coagulation being measured with thromboelastometry and Sonoclot. Multiplate indicated decreased platelet aggregation over time, without any effect of in vitro added desmopressin.